Analysis of Job Satisfaction Factor - Herminda, Herminda; Endang Suryani, Rahayu; Muksin, Abdullah; Adzkia, Marsya (Dinasti International Journal of Management Science, 2024)
The purpose of this research is to determine the influence of workload, human relations, and work-life balance on employee job satisfaction at PT. with a population of 119 employees and a sample of 92 respondents. This research uses quantitative methods, namely the study of the relationship between two or more variables. The data was analyzed using the SmartPLS version 4 program. Based on the results of tests carried out on all variables, it is known that partially there is a significant influence between workload variables on employee job satisfaction, as well as the human relations variable on job satisfaction. The work-life balance variable also significantly influences job satisfaction. This is proven by the Adjusted R² value of 0.660, meaning that job satisfaction can be explained by the three factors that influence employee performance (67.1% and the remaining 32.9% is influenced by other factors outside the variables of this research.